A unipolar thin‐film transistor‐based amplifier with enhanced DC offset suppression - Yuming Xu; Bin Li; Wei Zhong; Sunbin Deng; Houbo Fan; Zhaohui Wu; Fion Sze Yan Yeung; Hoi Sing Kwok; Rongsheng Chen (Electronics Letters, 2021)
Abstract This letter proposes a unipolar thin‐film transistor (TFT)‐based amplifier design that can provide enhanced DC offset suppression. The amplifier consists of an input AC coupling network and a capacitor bootstrap amplifier. By making the first pole of the input AC‐coupling network coincide with that of the capacitor bootstrap amplifier, a DC offset suppression capability of 40 dB/dec, which is 2× higher than that of the prior arts, can be obtained. An implementation is also proposed and a Rensselaer Polytechnic Institute (RPI) TFT model whose parameters are turned to fit the measured data of our metal‐oxide TFT is used to simulate the circuit. Simulation results show that the implementation has 31 dB midband gain, 0.5 Hz–5 kHz bandwidth, 300 μW power consumptions, and the expected 40 dB/dec DC offset suppression. This design is suitable for applications that need to block large DC interference, such as sensor readout amplifiers.